Behaviors Related to Wastewater Drainage Conditions in Pantai Cermin District - Sadilla Fitri; Linda Handayani; Yuniarti, Elsa; Barlian E (CV. CENDIKIA JENIUS INDONESIA, 2024)
The improper or inefficient treatment of domestic wastewater can contaminate receiving water bodies, particularly when the wastewater contains hazardous chemicals that are difficult to decompose. In the Pantai Cermin District, 70% of wastewater drainage systems (SPAL) fail to meet sanitation standards. This study aims to describe community behaviors related to the condition of domestic SPAL in Pantai Cermin District in 2024. A descriptive design with a cross-sectional approach was employed, conducted from January to June 2024. The study involved 100 households or housewives selected using stratified random sampling. The findings reveal that substandard physical conditions of SPAL were most prevalent among groups with low knowledge levels (72%), negative attitudes (69%), and poor perceptions (71%). Conclusion: The analysis indicates a significant relationship between knowledge level, attitude, perception, and the guidance provided by officers with the physical condition of domestic SPAL. Recommendations include enhancing educational programs, raising awareness, fostering community participation, and providing recognition to community groups committed to SPAL management at the local level.